ANALYSIS OF PATIENT SAFETY CULTURE FOR QUALITY IMPROVEMENT: A REPEATED CROSS-SECTIONAL STUDY - Ineza, Marina; Michael, Abraham; Sagala, Melinda (Universitas Airlangga, 2026)
Background: Patient safety culture is a key determinant of healthcare quality, reflecting shared values and practices that support safe care delivery. This study aimed to evaluate changes in patient safety culture and identify priority areas for improvement using repeated survey measurements. Methods:A quantitative descriptive cross-sectional design with repeated measurement was applied. The study included 207 healthcare and non-healthcare staff with at least one year of work experience, selected using a total sampling approach. Data were collected between June and August 2025 using a standardized 42-item instrument covering 10 dimensions of patient safety culture. Responses were measured using a five-point Likert scale. Descriptive analysis was conducted by calculating the percentage of positive responses and comparing results across two measurement periods. Results: The overall positive response rate increased from 55.2% to 64.8%, indicating improvement across most dimensions. The largest increases were observed in communication about errors, incident reporting, and teamwork, reflecting stronger openness and collaboration. Organizational learning also remained high. However, staffing and workload showed minimal improvement and remained the lowest scoring dimension. Nonpunitive response to errors and management support also showed comparatively lower scores. Conclusions: The findings demonstrate measurable improvement in patient safety culture over time, particularly in communication and teamwork domains. However, structural challenges such as staffing and organizational support persist. Strengthening leadership engagement, promoting a nonpunitive environment, and improving workforce management are essential to sustain long-term improvements in patient safety and healthcare quality.